Practicality of Causalytic Model Learning Integrated to Character Values Assisted by Go-Lab Platform to Improve Students' Problem Solving and Creative Thinking Abilities - Huraiza Mahmudah; Joni Rokhmat; Kosim; Hisbulloh Als Mustofa (International Journal of Contextual Science Education, 2024)
This research aims to develop a causalytic model learning integrated of character values assisted by Go-Lab platform to improve students' problem solving and creative thinking abilities. This development research procedure refers to the steps in developing a 4D model which consists of four main stages, namely defining, designing, developing and disseminating. The practicality test is carried out after the definition and design stages are completed. The practicality test instrument consists of an observation sheet on learning implementation as well as a teacher and student response questionnaire. The observers involved in filling out the observation sheet for learning implementation were 1 teacher of science and 20 students in class VIII-C at State Junior High School (SMPN) 3 Labuapi. Meanwhile, the observers involved in filling out the response questionnaire were 3 teachers of science and 20 students in class VIII-C at SMPN 3 Labuapi. Learning tools are said to be practical if the observers' assessments state that the learning tools can be applied. The results of the analysis of observations of learning implementation by teachers and students obtained an average percentage of 97.08% and 96.88% in very practical category. Meanwhile, the results of the analysis of teacher and student responses obtained an average percentage of 90.00% and 98.00% in very practical category. This shows that the learning tools developed are easy to use, easy to interpret, and provide benefits for teachers and students.